Bioadhesive floating microsponges of cinnarizine as novel gastroretentive delivery: Capmul GMO bioadhesive coating versus acconon MC 8‑2 EP/NF with intrinsic bioadhesive property - Raghuvanshi, Smita; Pathak, Kamla (International Journal of Pharmaceutical Investigation)
Introduction: The study was aimed at the development of low-density gastroretentive bioadhesive microsponges of cinnarizine by two-pronged approach (i) coating with bioadhesive material and (ii) exploration of acconon MC 8-2 EP/NF as bioadhesive raw material for fabrication. Materials and Methods: Microsponges were prepared by quasi-emulsion solvent diffusion method using 32 factorial design. Capmul GMO was employed for bioadhesive coating. In parallel, potential of acconon for the fabrication of bioadhesive floating microsponges (A8) was assessed. Results: Formulation with entrapment efficiency = 82.4 ± 3.4%, buoyancy = 82.3 ± 2.5%, and correlation of drug release (CDR8h) = 88.7% ± 2.9% was selected as optimized formulation (F8) and subjected to bioadhesive coating (BF8). The %CDR8h for A8 was similar to BF8 (87.2% ± 3.5%). Dynamic in vitro bioadhesion test revealed comparable bioadhesivity with BF8. The ex vivo permeation across gastric mucin displayed 63.16% for BF8 against 56.74% from A8; affirmed the bioadhesivity of both approaches. Conclusion: The study concluded with the development of novel bioadhesive floating microsponges of cinnarizine employing capmul GMO as bioadhesive coating material and confirmed the viability of acconon MC 8‑2EP/NF as bioadhesive raw material for sustained targeted delivery of drug.
Keywords: Acconon MC8-2 EP/NF; capmul GMO; cinnarizine; dynamic in vitro bioadhesion test; ex vivo permeation; microsponges